Fetuin-B links nonalcoholic fatty liver disease to type 2 diabetes via inducing insulin resistance: Association and path analyses. (August 2018) - Li, Zhibin; Lin, Mingzhu; Liu, Changqin; Wang, Dongmei; Shi, Xiulin; Chen, Zheng; Liu, Yongwen; Yang, Shuyu; Li, Xuejun
Abstract: Objective: Laboratory models suggested that Fetuin-B impaired insulin action in myotubes and hepatocytes and caused glucose intolerance in mice. We aimed to explore the independent associations and pathways among serum Fetuin-B, nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D). Methods: A cross-sectional study of 1318 obese adults who underwent serum Fetuin-B test and hepatic ultrasonography scanning was conducted in Xiamen, China. Multivariable logistic regression was used to calculate adjusted odds ratio (OR) and 95% confidence intervals (CI) of serum Fetuin-B level and NAFLD for T2D in different models with adjustment for potential confounders. Structural equation modeling (SEM) was used to examine the paths among NAFLD, serum Fetuin-B, metabolic/insulin resistance syndrome and T2D. Results: Subjects with T2D or NAFLD showed significantly increased serum Fetuin-B levels compared to their controls (4.25 ± 1.35 vs. 4.08 ± 1.38 µg/ml for diabetes; and 4.26 ± 1.41 vs. 4.07 ± 1.33 µg/ml for NAFLD; both p-values < 0.05). NAFLD and higher serum Fetuin-B were significantly associated with higher risk of T2D with adjustment for sociodemographic and lifestyle habits; and the adjusted ORs (95%CIs) were 2.90 (2.17–3.87, p < 0.001) and 1.16 (1.01–1.32, p = 0.032), respectively. With further adjustment for metabolic/insulin resistance syndrome (BMI, systolic and diastolic BP, triglyceride, total cholesterol, HDL- and LDL-cholesterol, HOMA-IR and serum uric acid), NAFLD but not serum Fetuin-B was significantly associated with increased risk of T2D (ORs (95%CIs): 1.58 (1.12–2.21, p = 0.009) and 1.07 (0.92–1.23, p = 0.384), respectively). A one pathway model by using SEM fitted well (χ 2 = 497.92, p < 0.001; CFI = 0.965; TLI = 0.926; and RMSEA = 0.097) and showed that NAFLD increased serum Fetuin-B and elevated Fetuin-B increased fasting insulin level, which in turn induced insulin resistance and T2D. Besides, NAFLD increased the risk of T2D directly in addition to its indirect effects of inducing metabolic/insulin resistance syndrome which in turn increased the risk of T2D. Conclusions: Fetuin-B links NAFLD to T2D via inducing insulin resistance, and NAFLD contributes to the pathogenesis of T2D via multiple mechanisms.